Challenges to discussing palliative care with people experiencing homelessness: a qualitative study. Issue 11 (28th November 2017) - Hudson, Briony F; Shulman, Caroline; Low, Joseph; Hewett, Nigel; Daley, Julian; Davis, Sarah; Brophy, Nimah; Howard, Diana; Vivat, Bella; Kennedy, Peter; Stone, Patrick
Abstract : Objectives: To explore the views and experiences of people who are homeless and those supporting them regarding conversations and approaches to palliative care Setting: Data were collected between October 2015 and October 2016 in homeless hostels and day centres and with staff from primary and secondary healthcare providers and social care services from three London boroughs. Participants: People experiencing homelessness (n=28), formerly homeless people (n=10), health and social care providers (n=48), hostel staff (n=30) and outreach staff (n=10). Methods: In this qualitative descriptive study, participants were recruited to interviews and focus groups across three London boroughs. Views and experiences of end-of-life care were explored with people with personal experience of homelessness, health and social care professionals and hostel and outreach staff. Saturation was reached when no new themes emerged from discussions. Results: 28 focus groups and 10 individual interviews were conducted. Participants highlighted that conversations exploring future care preferences and palliative care with people experiencing homelessness are rare. Themes identified as challenges to such conversations included attitudes to death; the recovery focused nature of services for people experiencing homelessness; uncertainty regarding prognosis and place of care; and fear of negative impact. Conclusions: This research highlights the need for a different approach to supporting people who are homeless and are experiencing advanced ill health, one that incorporates uncertainty and promotes well-being, dignity and choice. We propose parallel planning and mapping as a way of working with uncertainty. We acknowledge that these approaches will not always be straightforward, nor will they be suitable for everyone, yet moving the focus of conversations about the future away from death and dying, towards the present and the future may facilitate conversations and enable the wishes of people who are homeless to be known and explored.